„WĘGIERSKI ŚLAD”.Z WIOSNY LUDÓW (1848-1849) NA OBSZARZE KORONY ŚW. STEFANA DO POLSKIEGO POWSTANIA (1863-1863), CZ. I - Buława, Adam (Saeculum Christianum. Pismo Historyczne, 2017)
During the Spring of Nations in the lands of the Crown of St. Stefan (1848-1849) traditional ties of friendship, with the possibility of a military confrontation occurring with one, two invaders attracted a large crowd of Polish volunteers for the formation of the Hungarian honveds. About 4,000 Poles were fighting directly in the ranks of the revolutionary army, and enrolled to the national legions under the command of Generals Joseph Wysocki alongside the Transylvanian Army Fieldmarshal Joseph Bem. Among them, about 20 individuals who will be later on commanders of the guerrilla armed troops of the January Uprising (1863-1864). For this reason, it is worth recalling the experience that the military group acquired during the battles for the Hungarian Plain, Slovakia, Bukovina, Moldavia, Banat, Backa and Transylvania.